Respostas
respondido por:
15
m+5n=5 --> m=5-5n
4(5-5n)+10n=16
20-20n+10n=16
-10n=16-20
-10n=-4
n=4/10
m=-5(4/10)+5
m=-20/10 +5
m=-2 +5
m=3
3+4/10=
continue agr :)
4(5-5n)+10n=16
20-20n+10n=16
-10n=16-20
-10n=-4
n=4/10
m=-5(4/10)+5
m=-20/10 +5
m=-2 +5
m=3
3+4/10=
continue agr :)
respondido por:
5
m+ n = 5
4m+ 10n = 16
multipica a primeira equaçao por -4 para eliminar uma das variaveis
-4m - 4 = -20
4m + 10 n = 16
0 + 6n = - 4
n= - 4\ 6
m+ ( - 4\ 6 ) = 5
m = 5 + 4\6
m= 9\ 6
4m+ 10n = 16
multipica a primeira equaçao por -4 para eliminar uma das variaveis
-4m - 4 = -20
4m + 10 n = 16
0 + 6n = - 4
n= - 4\ 6
m+ ( - 4\ 6 ) = 5
m = 5 + 4\6
m= 9\ 6
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás